Wearable system for measuring three-dimensional reaction forces and moments using six-axis force sensors during skating - Hara, Y.; Takahashi, T.; Haraguchi, N.; Koshio, T.; Takeuchi, Y.; Hase, K. (Journal of Biomechanical Science and Engineering, 2024)
Recent advancements in motion measurement systems have facilitated the analysis of kinematic techniques in sports, emphasizing the importance of motion control for performance enhancement. Ground reaction forces and moments are crucial in biomechanical analysis, and are typically measured using force plates. However, conventional force plates pose limitations in winter sports due to their impracticality on ice. To address this, various methods have been explored, including skates equipped with strain gauges and pressure-sensitive insoles. Despite advancements, simultaneous measurement of forces and moments in three axes remains a challenge. In this study, we developed a new wearable system capable of comprehensively measuring the forces and moments during skating by attaching three wearable force plates between the boot and the blade. The precision of this measurement system was validated through an experiment employing a conventional force plate, demonstrating its high accuracy. On-ice trials confirmed the system's efficacy in capturing dynamic movements like forward sliding and half-turn jumps. The six-component force was successfully measured during skating motions, a task that is challenging with conventional systems. This system offers a promising avenue for nuanced biomechanical analysis in figure skating, facilitating insights into performance optimization and injury prevention.